Liquid chromatograph-mass spectrometry metabolomics uncovers potential biomarkers of semen cryo-injury in goats - Shun Wu; Guolin Chen; Siyuan Zhan; Linjie Wang; Jiaxue Cao; Jiazhong Guo; Li Li; Hongping Zhang; Lili Niu; Tao Zhong (Animal Bioscience)
Objective Semen cryopreservation acts a crucial role in enhancing breed improvement and conserving genetic resources. However, it often leads to decreased sperm activity and reduced pregnancy rates. Despite significant advancements in semen freezing techniques for goats, the precise factors and mechanisms causing cryo-injury remain unclear. Methods In this study, we examined the motility characteristics of fresh semen versus frozen-thawed semen and investigated changes in the metabolite profiles of seminal plasma using liquid chromatograph-mass spectrometry. Results A total of 364 differentially expressed metabolites (DEMs) were identified between fresh and frozen-thawed semen samples. Among these, 185 metabolites were significantly up-regulated, while 179 were down-regulated (p<0.05). The majority of these DEMs belonged to lipids and lipid-like molecules, as well as organic acids and derivatives. The Kyoto encyclopedia of genes and genomes indicated that these DEMs were primarily involved in pathways related to amino acid synthesis and metabolism. Additionally, metabolite set enrichment analysis underscored the critical role of amino acid synthesis and metabolic pathways in semen cryopreservation. Specific metabolites such as alanine, proline, phenylalanine, tryptophan, tyrosine, adenosine, citric acid, flavin adenine dinucleotide, and choline emerged as potential biomarkers for sperm cryo-injury in goats. Conclusion These findings provide valuable insights into enhancing the quality of semen cryopreservation in goats, contributing to improved breeding and genetic resource conservation efforts.